MSME Strategies in Facing Digital Disruption: A Study on Creative Industry - Nampira, Ardi Azhar; Nasution, Edwin Sugesti; Moktar, Brilian; Harja, Ngiw Aman (West Science Business and Management, 2025)
Digital disruption presents both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's creative industry. This qualitative study explores the strategies adopted by MSMEs to adapt to these changes through in-depth interviews with 10 MSME owners from various creative sectors. The findings reveal that MSMEs leverage digital platforms, innovate their offerings, invest in capacity building, and establish collaborative networks to navigate digital disruption. However, they face significant challenges, including technological barriers, financial constraints, market saturation, and inadequate infrastructure. Despite these challenges, MSME owners expressed optimism about leveraging emerging technologies for growth. The study underscores the need for targeted policy interventions and capacity-building initiatives to support MSME sustainability in the digital era. These findings provide valuable insights for policymakers, industry stakeholders, and MSMEs striving to thrive amid digital transformation.